Resposta :
Resposta:
Explicação passo a passo:
Resolvendo:
a)
[tex]\left \{ {{x+y=10-->x=10-y} \atop {2x-3y=5\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:}} \right. \\\\2x-3y=5\\2(10-y)-3y=5\\20-2y-3y=5\\-5y=-15\\y=3\\\\x+y=10\\x+3=10\\x=7[/tex]
S = { ( 7; 3 ) }
b)
[tex]\left \{ {{2x+y=-6\:\:-->y=-6-2x} \atop {3x-2y=4\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:}} \right. \\\\3x-2y=4\\3x-2(-6-2x)=4\\3x-(-12-4x)=4\\3x+12+4x=4\\7x=-8\\x=-\frac{8}{7}\\\\2x+y=-6\\2(-\frac{8}{7} )+y=-6\\-\frac{16}{7} +y=-6\\y=-6+\frac{16}{7} \\y=\frac{-42+16}{7} \\y=\frac{-26}{7}[/tex]
S = { ( [tex]-\frac{8}{7}[/tex]; [tex]-\frac{26}{7}[/tex] ) }
Espero ter ajudado!
Desculpe qualquer erro.